Sekolah Bertaraf Internasional dalam Perspektif Hak Asasi Manusia - Nugroho, Okky Chahyo (Jurnal HAM, 2013)
This study is a continued and multi-years research. In the first year, the data reveal about the management of flagship high school in Jakarta, West Java, Yogyakarta, and South Sulawesi, based on indicators of human rights-based education, and reveal the presence of data and international schools management in Jakarta. Based on the findings in the first year (2009), there has been three books that will be used as a guideline in the developing International Standard School (SBI), namely: (1) SBI development handbook (2) SBI curriculum development handbook, and (3 ) SBI workforce manual. Subsequently in the second year, third guidebook will be piloted in schools that are potential to become SBI. In addition, in the second year (2010) there will be: (1) SBI manual on students selection, (2) SBI teaching and learning process implementation guidebook, and (3) SBI finance guidebook. These handbooks will complement the development of the entire system in ac- cordance with SBI rights-based education parameters. This research is a descriptive and evaluative research and was taken place in RSBI high school in Yogyakarta Province (SMAN 3 Yogyakarta, Yogyakarta SMAN 8, and SMA Muhammadiyah 2). The evaluative research is used to determine the success of the application of International School Development Handbook, Man Power Manual, and Curriculum Handbook. The experi- ment lasted for 8 months, from February to November 2010.